Practical Tracking Control of Cable-Driven Robots Using Adaptive Nonsingular Fast Terminal Sliding Mode - Yaoyao Wang (IEEE Access, 2018)
In this paper, a novel robust control scheme is developed for the trajectory tracking control purpose of cable-driven robots under complex lumped uncertainties. The proposed control scheme utilizes time-delay estimation (TDE) technique to obtain the lumped unknown system dynamics; and therefore ensures an attractive model-free advantage. A novel adaptive nonsingular fast terminal sliding mode (ANFTSM) manifold is designed considering its uncertainties, which is estimated by a newly designed adaptive law. Afterward, corresponding TDE-based ANFTSM control scheme is proposed. The proposed control scheme requires no system dynamics and therefore is easy to use in complicated practical applications benefitting from TDE technique. Meanwhile, high tracking accuracy and fast dynamical response can be effectively ensured using the proposed ANFTSM manifold. Stability of the closed-loop control system is proved through Lyapunov method. Finally, comparative simulations and experiments were conducted to demonstrate the superiorities of our proposed method over the existing ones.